ChemInform Abstract: A Simple One‐Pot Synthesis of Quinoline‐4‐carboxylic Acid Derivatives by Pfitzinger Reaction of Isatin with Ketones in Water. Issue 29 (1st July 2013) - Lv, Qinghua; Fang, Lizhen; Wang, Pengfei; Lu, Chenjuan; Yan, Fulin
Abstract: An optimized procedure is given for the reaction of isatin with ketones to afford title quinoline compounds (III) which are otherwise difficult to prepare.